PENGEMBANGAN CORAL NURSERY CENTER BERBASIS MASYARAKAT UNTUK PENGUATAN WISATA SELAM DI PULAU KARAMPUANG, MAMUJU - Arwin, Arwin; Israwahyudi, Israwahyudi; Basri, Subianto; Gufran, Muhammad; Irmanto, Irmanto (Universitas Mataram, 2025)
Tourism awareness groups (POKDARWIS) are independent community groups that play an active role in the development and preservation of tourism potential in their villages or areas. POKDARWIS Ujung Bulo Marine Tourism Karampuang Island Village is a tourism awareness group established by the Mamuju Regency Tourism and Culture Office on January 2, 2023, based on Decree No. 900/02. a/I/2023/PARBUD. It consists of 20 members, including the chairman. The purpose of this PKM activity is to increase awareness and knowledge among partners about the preservation of coral reef ecosystems through sustainable coral nursery centers, and to develop the potential for sustainable diving tourism based on coral reef conservation. The implementation method used at the Coral Nursery Center is carried out in the following stages: preparation, socialization/focus group discussion, training, creation of the Coral Nursery Center, monitoring, and evaluation. The community service was held on July 22-23, 2025, in Karampuang Island Village, which was attended by 25 participants at the focus group discussion stage and 10 partner representatives at the stage of creating a coral nursery center. The number of rope stretches made was 5, with each rope installed with 20 coral saplings, resulting in a total of 100 coral saplings installed. The results of the PKM activities carried out have yielded an increase in partners' knowledge and understanding of the importance of coral reef ecosystems for human life. Based on the posttest conducted after the activity, the increase in knowledge on the FGD material was 85.81%, the implementation of transplantation was 71.56% and the coral health monitoring process was 71.56%. To enable partners to effectively manage coral nursery centers and implement coral adoption programs, thereby increasing the potential for education-based marine tourism and attracting more tourists. The survival of coral fragments in the coral nursery centers is 70%. In the coral adoption program, the number of potential tourists involved over the course of one year following the implementation of the activity is targeted at 69 people.